Pengaruh People Power Dalam Peradilan Di Indonesia - Filip Jaya Saputra; Ollanisa Putri; Pebri Nopita Sari; Alimni Alimni; Ismail Ismail (Qiyas : Jurnal Hukum Islam dan Peradilan, 2023)
Abstract: The role of society in law enforcement in this country is very important. This role needs to be supported by discipline in complying with established laws and regulations. This article, which uses a normative legal research methodology, concludes that, in fact, the content of the rule of law applied in Indonesia contains the principle of the dignity of man, which contains the principles of democracy regarding the ideas of constitutionalism and a government that is given limited authority. With the rule of law, justice and people's welfare can be achieved, because there is the right of the people to participate in voicing justice in accordance with the fifth Pancasila precept which reads "social justice for all Indonesian people".Keywords: People Power; Justice.